The Story of Christmas - Bamfield, Katherine B. (The Medici Press, 1952)
The Bible tells us that in the Beginning God created Man in His own image. But very soon men and women began to do things God had told them not to do, and with their disobedience sin came into the beautiful world that God had made. God was very sorry and He pitied mankind and made a promise that in His own time He would send a Saviour to help them...
Keywords: Bible Stories; Juvenile Fiction; Religion